The Numerical Convergence of the Landau-Lifshitz Equations and Its Simulation - Penghong Zhong; Shu Wang; Ke Wang; Yiping Bai (Discrete Dynamics in Nature and Society)
A difference scheme of Landau-Lifshitz (LL for short) equations is studied. Their convergence and stability are proved. Furthermore, a new solution of LL equation is given for testing our scheme. At the end, three subcases of this LL equation are concerned about, and some properties about these equations are shown by a numeric simulation way.